INSTRUMENTS TO PROMOTE SOLAR ENERGY DEVELOPMENT IN BRAZIL: POSSIBILITIES TO URBAN DECONCENTRATION INDUCTION AND TO REGIONAL INEQUALITIES REDUCTION - Cavalcante, Denise Lucena; de Moraes e Dantas, Eric (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2019)
This study is contextualized in the Brazilian photovoltaic energy matrix development, addressing possibilities of fostering its use by solar industries, by micro and small enterprises and by farmers as an alternative to stimulate them to settle besides metropolis, in order to show it's potential to act as an instrument in the urban deconcentration process. The increasing global population concentration in metropolis in one of the greatest environmental challenge in this century. According to the UN, by 2050, about 6.4 billion people will live in urban centers, with an estimated generation of 70% of CO2 emissions. Brazilian context isn't different. With a huge area of 8,514,876 km2, more than 60% of its population is concentrated in coastal zone. In order to make significant changes in our urban scenarios, it's necessary to promote policies of better use of the countryside space, which could enable alternatives: permanence in the countryside or even a well-structured large urban centers exodus